FAKTOR-FAKTOR YANG MEMENGARUHI FINANCIAL DISTRESS DENGAN FIRM SIZE SEBAGAI VARIABEL MODERASI - Cahyadi, Vinny; Viriany, Viriany (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
The purpose of this research is to obtain empirical evidence on the impact of profitability, liquidity and leverage on financial distress with firm size as moderating variable in the manufacturing companies food and beverages sub-sector listed on the Indonesia Stock Exchange during 2019-2021 based on Jakarta Stock Industrial Classification (JASICA). This research use purposive sampling method to obtains 39 sample data from 13 manufacturing companies food and beverages sub-sector. The analytical technique used in this research is moderated regression analysis (MRA). This research used E-views 12 SV to analyze the panel data. As a result, profitability and liquidity did not significantly affected the financial distress, but leverage has a significant negative impact on financial distress. Firm size is able to moderate profitability and leverage on financial distress, while firm size doesn’t be able to moderates the impact of liquidity on financial distress. The implication of this study are the need to increase the effectiveness of assets owned by the companies and the need of company management ability to manage the debt owned that will be a positive signal for investors and prevent company from financial distress risk.